Differential Mitochondrial DNA and Gene Expression in Inherited Retinal Dysplasia in Miniature Schnauzer Dogs - Appleyard, Greg D; Forsyth, George W; Kiehlbauch, Laura M; Sigfrid, Kristen N; Hanik, Heather L. J; Quon, Anita; Loewen, Matthew E; Grahn, Bruce H (Investigative ophthalmology & visual science, 2006)
To investigate the molecular basis of inherited retinal dysplasia in miniature Schnauzers. Retina and retinal pigment epithelial tissues were collected from canine subjects at the age of 3 weeks. Total RNA isolated from these tissues was reverse transcribed to make representative cDNA pools that were compared for differences in gene expression by using a subtractive hybridization technique referred to as representational difference analysis (RDA). Expression differences identified by RDA were confirmed and quantified by real-time reverse-transcription PCR. Mitochondrial morphology from leukocytes and skeletal muscle of normal and affected miniature Schnauzers was examined by transmission electron microscopy. RDA screening of retinal pigment epithelial cDNA identified differences in mRNA transcript coding for two mitochondrial (mt) proteins--cytochrome oxidase subunit 1 and NADH dehydrogenase subunit 6--in affected dogs. Contrary to expectations, these identified sequences did not contain mutations. Based on the implication of mt-DNA-encoded proteins by the RDA experiments we used real-time PCR to compare the relative amounts of mt-DNA template in white blood cells from normal and affected dogs. White blood cells of affected dogs contained less than 30% of the normal amount of two specific mtDNA sequences, compared with the content of the nuclear-encoded glyceraldehyde-3-phosphate dehydrogenase (GA-3-PDH) reference gene. Retina and RPE tissue from affected dogs had reduced mRNA transcript levels for the two mitochondrial genes detected in the RDA experiment. Transcript levels for another mtDNA-encoded gene as well as the nuclear-encoded mitochondrial Tfam transcription factor were reduced in these tissues in affected dogs. Mitochondria from affected dogs were reduced in number and size and were unusually electron dense. Reduced levels of nuclear and mitochondrial transcripts in the retina and RPE of miniature Schnauzers affected with retinal dysplasia suggest that the pathogenesis of the disorder may arise from a lowered energy supply to the retina and RPE.